Liberalisasi Pertanian Versus Kesejahteraan Petani: Upaya Mencari Jalan Tengah - Achmad Faidy Suja’ie; Nian Riawati (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2019)
Agricultural liberalization continued controversy. Intensification of agriculture industry in Indonesia has not been able to welfare of farmers. Thus, the application of agricultural technology is always faced to the welfare of farmers. It reviews the debate both of them by perspective of structuralism to found a positive correlation between them. This condition is to offers an alternative solution for industrial agriculture versus the welfare of farmers.